1998
DOI: 10.1046/j.1471-4159.1998.70010171.x
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase Cγ1 in Bovine Rod Outer Segments: Immunolocalization and Light‐Dependent Binding to Membranes

Abstract: We have investigated the isozymes of a phosphoinositide‐specific phospholipase C (PLC) in bovine retina using several monoclonal antisera to PLCβ1, γ1, and δ1. Immunoblot analysis showed that all three isozymes were present in the retina. Immunocytochemical localization in frozen bovine retina sections showed that PLCγ1 was present in the photoreceptor cell layer, outer plexiform cell layer, inner plexiform cell layer, and ganglion cell layer. Immunoreaction within the photoreceptor cell layer was dependent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 21 publications
3
28
0
Order By: Relevance
“…A neuroprotective role associated with PI3K pathway activation was suggested ( 212 ). As was previously mentioned (see above), LROS were found to have higher PLC ␥ 1 activity than DROS and a higher PLC ␥ 1 was associated with LROS ( 69 ). These results are in accordance with results from Ilincheta de Boschero and Giusto ( 74 ) who found that membranes obtained from DROS washed in dark with low ionic strength buffer (5Dm), show higher polyphosphoinositide [PI(4)P and PI(4,5)P 2 ] phosphorylation with respect to that found in membranes obtained from DROS exposed to light and washed in light with low ionic strength buffer (5Lm).…”
Section: Downloaded Frommentioning
confidence: 66%
See 3 more Smart Citations
“…A neuroprotective role associated with PI3K pathway activation was suggested ( 212 ). As was previously mentioned (see above), LROS were found to have higher PLC ␥ 1 activity than DROS and a higher PLC ␥ 1 was associated with LROS ( 69 ). These results are in accordance with results from Ilincheta de Boschero and Giusto ( 74 ) who found that membranes obtained from DROS washed in dark with low ionic strength buffer (5Dm), show higher polyphosphoinositide [PI(4)P and PI(4,5)P 2 ] phosphorylation with respect to that found in membranes obtained from DROS exposed to light and washed in light with low ionic strength buffer (5Lm).…”
Section: Downloaded Frommentioning
confidence: 66%
“…The activities of enzymes involved in ROS phospholipid turnover such as PLC ( 3,46,68,69 ), phospholipase A2 (PLA2) ( 70 ), phosphatidylethanolamine N-methyltransferase (PEMT) ( 71 ), diacylglycerol kinase (DAGK) (72)(73)(74)(75), lipid phosphate phosphatase (LPP) ( 76 ), diacylglycerol lipase (DAGL) ( 77,78 ), PI synthase ( 79 ), phosphoinositide-3-kinase (PI3K) ( 80,81 ), and PLD ( 82 ) have been reported to be modulated by light. Detailed studies on PI3K signaling are described by Rajala in the thematic review in this series on PI3K in the vertebrate retina.…”
Section: Light Regulation Of Enzymes Related To the Generation Of Secmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data suggest that Src is a light-activated tyrosine kinase in photoreceptor cells and may, in part, be responsible for the increase in tyrosine phosphorylation in ROS membranes. Several putative Tyr(P) substrates have been identified in ROS, including phosphatidylinositol 3-kinase (28), SHP-2 (29), transducin ␣ (19), and PLC␥ 1 , which binds to bleached ROS membranes in vitro and translocates from the inner and outer segments of photoreceptors in response to light adaptation in vitro (30). The possible regulation of the former enzymes by light in vivo is currently under investigation.…”
Section: Figmentioning
confidence: 99%